Using thermal imaging to assess the effect of classical massage on selected physiological parameters of upper limbs - Boguszewski Dariusz; Adamczyk Jakub Grzegorz; Urbańska Nina; Mrozek Natalia; Piejko Karolina; Janicka Małgorzata; Białoszewski Dariusz (Sciendo, 2014)
Study aim: the aim of this study was to assess the relationship between classical sport massage of the hand and the forearm and the surface temperature of upper limb muscles, and between hand grip strength and the range of motion in the radiocarpal joint.